Prevalance of Dirofilaria immitis in dogs in Johor Bharu, Malaysia. - Ng, Kit Lin; Abdullah Sani, Rehana; Lee, Ee Liang (2011)
This study was conducted to determine the prevalence of Dirofilaria immitis in dogs in Johor Bahru, Malaysia. The diagnostic techniques employed were wet blood mount, Knott’s concentration test and two heartworm antigen test kits (IDEXX Canine SNAP® 4Dx and RapiGEN®). This study also attempted to compare the two test kits used and identify the microfilaria isolated. Blood from 100 pet and 50 stray dogs in Johor Bahru were examined. The prevalence of heartworm in pet and stray dogs in this study were 1 and 2% respectively. The overall prevalence of Dirofilaria immitis in dogs in Johor Bahru was 1.33% (2/150) and the microfilaria was identified as Dirofilaria immitis. Since there was only one false-negative result from RapiGEN® test kit, sensitivity between the two test kits could not be compared. The low prevalence of Dirofilaria immitis found in this study confirmed anecdotal evidence that the prevalence of Dirofilaria imminits in Dogs is low in Johor Bahru.